Financial Sustainability Of Company Limited By Guarantee Charities In Malaysia - Choy Sheung, Sharon Cheuk (2020)
Charities of all sizes play an essential role in society and economy, and provide social care and education, and they are now increasingly viewed as critical contributors to economic growth and social infrastructure; they also represent a substantial employer and a provider of services. Yet, charity failure has been a problem that has been plaguing developed countries and developing alike. In Malaysia, it has been reported that charities have difficulties in raising donations due to the difficult economic climate. In view of the foregoing, the purpose of this study is to determine the current level of charity financial sustainability, and to discover the relationships amongst accountability, own income generation, revenue diversification, director tenure diversity, financial management capacity and organisation size, and how these relate to financial sustainability; the latter forms the theoretical framework of this study.